Truncation error estimation for Newton–Cotes quadrature formulas - Kostas Plukas; Danutė Plukienė (Lietuvos Matematikos Rinkinys)
Theoretical and practical aspects of truncation error estimation for Newton–Cotes quadrature formulas are discussed in this paper.